2018
DOI: 10.24112/jaes.020103
|View full text |Cite
|
Sign up to set email alerts
|

What Influences the Choice Between Private Car and Public Transport for Shopping Trips? Impact of Socio-economic and Built Environment Factors

Abstract: Shifting toward sustainable daily travel will play a significant role in the future of sustainable development and the lowering of carbon emissions. This study provides an in-depth comparison of transport mode choice and corresponding CO 2 emissions between private cars and public transport used for shopping trips based on individual data from a travel survey conducted in Shenyang, China. The analysis found that bus travel accounted for the majority of motorized transportation. Public transport users were clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…97 This is important because, as China is transitioning to a high-tech, service-based, and consumption-focused economy, 140 carbon emissions from the building and transportation sectors will become much more significant. 141,142 Fourth, the power of surveillance technologies as a policy instrument needs to be better harnessed. The rapid development of surveillance technologies, such as remote sensing and GPS tracking, has provided unprecedented surveillance power.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…97 This is important because, as China is transitioning to a high-tech, service-based, and consumption-focused economy, 140 carbon emissions from the building and transportation sectors will become much more significant. 141,142 Fourth, the power of surveillance technologies as a policy instrument needs to be better harnessed. The rapid development of surveillance technologies, such as remote sensing and GPS tracking, has provided unprecedented surveillance power.…”
Section: Discussionmentioning
confidence: 99%
“…97 This is important because, as China is transitioning to a high-tech, service-based, and consumption-focused economy, 140 carbon emissions from the building and transportation sectors will become much more significant. 141,142…”
Section: Discussionmentioning
confidence: 99%
“…A similar study in China applied a hierarchical structure model to forecast mode choice, and a logical relationship to determine the influential factors using existing trip survey data [22]. Another study in China used a binary logistic model to examine the influential factors on travelers choice between the modes of the private car and public transport [23]. It was found that travelers' gender and auto ownership were the most influential factors on choosing the private vehicle.…”
Section: Subjective Determinants On Mode Choicementioning
confidence: 99%
“…The shorter the distance between residents and public transportation, the more likely residents are to use public transportation for their travel. However, research suggests that living near a bus stop does not significantly alter residents' preference for private car travel [36,37]. Improved destination accessibility can shorten commuting distances and reduce the intensity of private car use among residents.…”
Section: Introductionmentioning
confidence: 99%